Cultural gateways - building partnerships for sustainable development in destination regions - Antonio Russo (European Regional Science Association (ERSA), 2005)
This paper introduces the main findings of the CULTURAL GATEWAYS project caried out during 2004-2005 by the author wiht a eserach fellowship at Universitat Autonoma, Barcelona. The aim of the project is the development of a sustainable urban-rural relationship in the organisation of tourist regions around main urban destination. The projects analyses existing visitation models and cognitive processes of visitors in main destinations, as well as existing organisations that produce culture in peripheral areas, elaborating strategies to promote and diffuse these less-known assets. A key motive is to build on the existing tourist potential, developing "gateways” (both physical and virtual) that reconnect the cultural heritage of peripheral communities to existing value chains. The departure point is that the preservation of cultural heritage through responsible tourism is the key to generating both wealth and well being in host communities. Experience demonstrates that host communities are better able to cope with existing problems and new challenges, when all concerned parties jointly attempt to find a balanced solution through mutual consultation, business-to-business co-operation and public-private partnerships. The main challenge to that respect is that many local communities do not realise the interest value that features of their local community may have to the outside world. It is believed that the "metropolitan” or "regional” dimension of tourism governance, and thus necessarily of cultural strategies, is the key to a more sustainable use of the heritage and cultural assets for community development. A restructured core-periphery visitation pattern benefits the communities involved, in terms of lower pressure levels and crowding of central destinations, of enhanced entrepreneurial capacity in rural areas, and of a more articulated visitor mobility on the territory, rebalancing the costs and revenues generated by tourism and boosting the spin-off potential of tourism in areas with a weak economic basis but rich in culture. On this account, ICT (Information and Communication Technologies) are seen as a promising tool that achieves a number of desirable outcomes: o global access to local cultural knowledge, o interactivity between the local cultural and foreign audiences with the establishment of "cultural empathy” between hosts and guests, o integration of the peripheral tourist areas in the distribution channels of core products, o empowerment and training for entrepreneurs in the cultural industries. The effects of global-urban-rural partnership through e-Strategies are tested in a number of pilot destination regions, including the Catalan and the Galician Communities in Spain and the Veneto Region in Italy. The project will analyse how the introduction of ICT tools for tourism and cultural marketing has changed (or is likely to change) visitors' attitudes and community involvement for a more sustainable tourism. An attempt will be made at generalising the results providing guidelines for regional managers.
Keywords: 330